Development of Web-Based Modules to Improve Digital Literacy and Learning Outcomes in Science Learning - Ismail, Muhammad Nur Khatir; Supeno, Supeno; Rusdianto, Rusdianto (Jurnal Paedagogy, 2024)
This study aims to produce e-modules for science lessons that are valid, practical, and effective to improve junior high school students' digital literacy and learning outcomes. This study used research and development methods with the ADDIE model. The data collection techniques were observation, interviews, validation sheets, student activity sheets using e-modules, learning outcomes tests, digital literacy assessment rubrics, student response questionnaires, and documentation. The data analysis techniques used in this study were validity test techniques, practicality tests and effectiveness tests. The results of the validation data analysis obtained a validation value of 91% with a very valid category, including aspects of content and construct validation. The practicality analysis results obtained a value of 91.20% with an efficient category. The results of the effectiveness analysis were based on the increase in learning outcomes, which resulted in an n-gain of 0.61 with a moderate category. Meanwhile, the results of the effectiveness analysis based on the ability of digital literacy indicators got an n-gain of 0.71 with a high category. The results of the effectiveness analysis were seen from student questionnaires, which scored 83.23% in the excellent category. Thus, the e-module product that has been developed is said to be feasible to be implemented in junior high school science learning to improve digital literacy and learning outcomes of junior high school students.